Unexpected high retention of 15N‐labeled nitrogen in a tropical legume forest under long‐term nitrogen enrichment. (28th November 2021) - Mao, Jinhua; Mao, Qinggong; Gundersen, Per; Gurmesa, Geshere A.; Zhang, Wei; Huang, Juan; Wang, Senhao; Li, Andi; Wang, Yufang; Guo, Yabing; Liu, Rongzhen; Mo, Jiangming; et al.
Abstract: The responses of forests to nitrogen (N) deposition largely depend on the fates of deposited N within the ecosystem. Nitrogen‐fixing legume trees widely occur in terrestrial forests, but the fates of deposited N in legume‐dominated forests remain unclear, which limit a global evaluation of N deposition impacts and feedbacks on carbon sequestration. Here, we performed the first ecosystem‐scale 15 N labeling experiment in a typical legume‐dominated forest as well as in a nearby non‐legume forest to determine the fates of N deposition between two different forest types and to explore their underlying mechanisms. The 15 N was sprayed bimonthly for 1 year to the forest floor in control and N addition (50 kg N ha −1 year −1 for 10 years) plots in both forests. We unexpectedly found a strong capacity of the legume forest to retain deposited N, with 75 ± 5% labeled N recovered in plants and soils, which was higher than that in the non‐legume forest (56 ± 4%). The higher 15 N recovery in legume forest was mainly driven by uptake by the legume trees, in which 15 N recovery was approximately 15% more than that in the nearby non‐legume trees. This indicates higher N‐demand by the legume than non‐legume trees. Mineral soil was the major sink for deposited N, with 39 ± 4% and 34 ± 3% labeled N retained in the legume and non‐legume forests, respectively. Moreover, N addition did not significantly change the 15 N recovery patterns of both forests. Overall, these findings indicate that legume‐dominated forests act as a strong sink for deposited N regardless of high soil N availability under long‐term atmospheric N deposition, which suggest a necessity to incorporate legume‐dominated forests into N‐cycling models of Earth systems to improve the understanding and prediction of terrestrial N budgets and the global N deposition effects. Abstract : Using the first ecosystem‐scale 15 N labeling experiment in a legume‐dominated forest ( Acacia auriculiformis ) as well as in a nearby non‐legume forest ( Eucalyptus urophylla ), we found that legume‐dominated forest was a strong short‐term sink for deposited N despite soil N richness under long‐term high N deposition. Legume forest showed unexpectedly higher retention capacity of the added 15 N than the non‐legume forest. The different 15 N recovery patterns between the legume and the non‐legume forests mainly resulted from higher N retention by the legume trees.